Are U.S. Nontariff Barriers Retaliatory? An Application of Extreme Bounds Analysis in the Tobit Model - Gawande, Kishore (The Review of Economics and Statistics, 1995)
The extreme bounds analysis in Leamer (1982) is extended to the Tobit model with censoring. The extension involves the simple modification of replacing the censored values of the dependent variable by their expectation conditional on the MLEs and using the negative of the Hessian evaluated at the MLEs in place of the inverse of the covariance matrix. The application of this method to a data set that pools U.S. nontariff barriers across industries and countries arrives at the surprisingly robust (to changes in the prior) conclusion that U.S. nontariff barriers against its largest trading partners are already significantly retaliatory. Copyright 1995 by MIT Press.